Raised LIGHT Levels in Pulmonary Arterial Hypertension: Potential Role in Thrombus Formation - Otterdal, Kari; Andreassen, Arne K; Yndestad, Arne; Oie, Erik; Sandberg, Wiggo J; Dahl, Christen P; Pedersen, Turid M; Ueland, Thor; Gullestad, Lars; Brosstad, Frank R; Aukrust, Pal; Damas, Jan K (American journal of respiratory and critical care medicine, 2008)
Thrombus formation and inflammation are involved in the pathogenesis of pulmonary arterial hypertension (PAH), and LIGHT (Lymphotoxin-like Inducible protein that competes with Glycoprotein D for Herpesvirus entry mediator on T lymphocytes) has been shown to promote vascular inflammation. We sought to investigate the role of the tumor necrosis factor superfamily ligand LIGHT in the pathogenesis of PAH. We studied 73 patients with severe PAH and 10 control subjects. LIGHT and pro- and antithrombotic markers were assessed by enzyme immunoassays. (1) Patients with idiopathic PAH (n = 21), patients with PAH related to risk factors or associated conditions (n = 31), and those with chronic thromboembolic PAH (n = 21) all had raised serum levels of LIGHT compared with control subjects (n = 10). (2) LIGHT levels in femoral artery were significantly related to mortality in the patients with PAH. (3) Immunostaining of LIGHT and its receptors was seen in alveolar macrophages, vascular smooth muscle cells, and endothelial cells in lungs from patients with PAH. (4) Thirteen patients received prostacyclin infusion (3 mo), and all showed hemodynamic improvement, accompanied by decreased LIGHT levels. (5) Prostacyclin abolished the release of LIGHT from activated platelets in vitro, suggesting that the decrease in LIGHT during prostacyclin therapy could involve direct effects on platelets. (6) LIGHT increased tissue factor and plasminogen activator inhibitor type 1 and decreased thrombomodulin levels in endothelial cells, inducing a prothrombotic state in these cells. Our findings suggest prothrombotic effects of LIGHT in PAH involving endothelium-related mechanisms, potentially contributing to the progression of this disorder.